The Relationship Between Age, Work Duration and Reactive Movement of Pressing Nozzle with Subjective Complaints of Carpal Tunnel Syndrome (CTS) in Fuel Filling Operator Officers at Yogyakarta City Gas Stations in 2019 - ZulArdi, Subhan; Solikhin, Dede (Periodicals of Occupational Safety and Health, 2024)
Background: Carpal Tunnel Syndrome (CTS) is a health problem caused by the compression or pinching of the median nerve that passes through the carpal tunnel in the upper extremities. Several subjective complaints of Carpal Tunnel Syndrome were found at three petrol stations in Yogyakarta City. In addition, subjective complaints of Carpal Tunnel Syndrome are also influenced by age, duration of work and repetitive movements. This study aims to determine the relationship between age, work duration and repetitive movements of pressing the nozzle with subjective complaints of Carpal Tunnel Syndrome in fuel filling operators at petrol stations. Methods: The type of research used is quantitative descriptive research with a cross sectional approach. This research was carried out at three Yogyakarta City petrol stations, namely Giwangan petrol station, Lempuyangan petrol station and Semaki petrol station with a research sample of 46 people. Data collection was carried out by questionnaire method about CTS subjective complaints to fuel filling operators. This study uses univariate, bivariate analysis and chi-square test. Results: It was found that there was a relationship between the age variable and the subjective complaints of CTS with a p-value of 0.005, there was a relationship between the variable of work duration and the subjective complaints of CTS with a p-value of 0.038 and there was a relationship between the variable of repetitive movements and the subjective complaints of CTS with a p-value of 0.038. Conclusion: Based on the results of the study, the variables of age, duration of work and repetitive movements of pressing the nozzle have a relationship with subjective complaints of CTS in fuel filling operators at three petrol stations in Yogyakarta City